Driving towards Precision Medicine for angioedema without wheals. (November 2019) - Germenis, Anastasios E.; Cicardi, Marco
Abstract: Evidence accumulated over the last two decades indicates that recurrent angioedema without wheals constitutes a diverse family of disorders with a much higher complexity than was previously regarded. Indicatively, during the last two years, novel variants of three genes other than SERPING1 and F12 have been identified in association with hereditary angioedema. Most interestingly, functional studies of at least one of these variants (the variant c.807G > T of ANGPT1 gene) imply the existence of a new disease endotype in which the altered bradykinin metabolism and function does not play a central role. Therefore, using conventional approaches, it seems that the complexity of this disease cannot be sufficiently elucidated and any attempt to interrelate its many diverse aspects seems unrealistic. Similar to other rare and chronic diseases, a Precision Medicine approach, discovering the right target and giving "the right drug, for the right patient, at the right time, every time" seems the optimal future practice. Herein, we review recent data challenging and dictating the need for a switch of angioedema research into high-throughput approaches and we present the expected advantages for better understanding of the disease and patients management. Highlights: Angioedema without wheals is becoming much more genetically complex than was initially considered. Variants in SERPING1, F12, ANGPT1, PLG and KNG1 genes are associated with hereditary angioedema. A new disease endotype has been uncovered in which the vasculature and not bradykinin is the central player. Environmental factors may exert a significant effect on the clinical expression of the disease. Angioedema could be considered as a prototype for the implementation of Precision Medicine.